Effects of Cement Dust on the Pulmonary Function Indices of Cement Factory Workers in Karachi (Medical Forum Monthly, 2024)
Objective: It has been observed that exposure to cement dust has been found to be associated with impaired pulmonary function and lung diseases. Therefore, this study aims to determine the effects of chronic exposure to cement dust on the pulmonary function of cement mill workers (non smokers) and comparing it to non-exposed otherwise matched individuals.Study Design: Cross sectional studyPlace and Duration of Study: the study has been completed in duration of 4 months and the data was collected from a cement factory of Karachi.Materials and Methods: A cross sectional study was carried out on a sample size of 100 cement mill workers who were divided into two groups of non-smoker exposed (n=46) and non-smoker non-exposed (n=54) workers and matched for age, height, weight, BMI, duration of work and their PEFR and FEV1 were observed using electronic peak flow meter.Results: It has been found that there was no difference in the age, work experience, height, weight and BMI between the two groups while statistically significant difference was found in FEV1 between the two groups, while PEFR was found to be insignificant.Conclusion: Occupational cement dust exposure is associated with impaired pulmonary functions which may lead to chronic lung diseases in these workers. This justifies the need to take preventive measures.